Leon Kirchner : composer, performer, and teacher - Riggs, Robert, 1946- (Eastman studies in music, 2010)
The life of American composer, pianist, conductor, and teacher Leon Kirchner (1919-2009) is detailed here alongside discussions of his work. In addition to Riggs's extensive interviews with the composer, the biography is documented with Kirchner's colorful correspondence from a roster of luminaries: Saul Bellow, Leonard Bernstein, Edward Cone, Aaron Copland, Darius Milhaud, Isaac Stern, Roger Sessions, and many others. Excerpts from Kirchner's own elegantly written essays and speeches complete the portrait and reveal his highly personal, romantic view of music as powerful art capable of endowi.